2021
DOI: 10.3390/jfb12020030
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Proliferation under Severely Hypoxic Microenvironments Using Cell-Laden Oxygenating Hydrogels

Abstract: Different strategies have been employed to provide adequate nutrients for engineered living tissues. These have mainly revolved around providing oxygen to alleviate the effects of chronic hypoxia or anoxia that result in necrosis or weak neovascularization, leading to failure of artificial tissue implants and hence poor clinical outcome. While different biomaterials have been used as oxygen generators for in vitro as well as in vivo applications, certain problems have hampered their wide application. Among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…We previously reported that OMPs-laden hydrogels alleviated anoxic stress in hydrogel-encapsulated hMSCs and significantly improved vascularization by increased VEGF secretion under anoxic conditions. [17,19,48] To study the alleviation of anoxic injury in response to MI, we assessed a combinatorial effect of hypoxic chemotaxis through the application of SDF to populate an anoxic cell-dead area with circulating stem cells, followed by hypoxic mediation to induce vascularization through OMP encapsulation in silk-based tissue adhesive hydrogels. As a first step, OMPs were synthesized using calcium peroxide (CPO) and polycaprolactone (PCL) following our previously developed protocols through a controllable and scalable water-in-oil-in-water double emulsion synthesis method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that OMPs-laden hydrogels alleviated anoxic stress in hydrogel-encapsulated hMSCs and significantly improved vascularization by increased VEGF secretion under anoxic conditions. [17,19,48] To study the alleviation of anoxic injury in response to MI, we assessed a combinatorial effect of hypoxic chemotaxis through the application of SDF to populate an anoxic cell-dead area with circulating stem cells, followed by hypoxic mediation to induce vascularization through OMP encapsulation in silk-based tissue adhesive hydrogels. As a first step, OMPs were synthesized using calcium peroxide (CPO) and polycaprolactone (PCL) following our previously developed protocols through a controllable and scalable water-in-oil-in-water double emulsion synthesis method.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported on the role of oxygen-releasing microparticles (OMPs) in the improvement of angiogenic/vasculogenic properties in human mesenchymal stem cell (hMSC)-laden engineered tissues under anoxic conditions via improved viability and paracrine effect of hMSCs in vitro and in vivo. [16][17][18][19] Since SDF is a chemokine secreted by hMSCs, we expect a combinatorial effect of SDF and OMPs to improve angiogenesis at the infarct site in an MI condition. It is, therefore, intuitive to locally alleviate hypoxic stress while reducing the vascularization time via cardioprotective and oxygenating hydrogels that are mechanically robust and biodegradable to eventually improve the survival and function of recruited cells at the injured area.…”
Section: Introductionmentioning
confidence: 99%
“…Injectable cryogels are formed with methacrylated hyaluronic acid and CaO 2 [89]. Cumulative release of H 2 O 2 is up to 468 μmol over 3 h. Microparticles (MPs) are formed with the encapsulation of CaO 2 in PCL, then formed composites with GelMA[90] and release O 2 up to 5 weeks[91]. Over 2 weeks, 2.5 μM of H 2 O 2 is released without the formation of MPs while 1.0 μM with the formation of MPs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study utilized microparticles (MPs) formed with the encapsulation of CaO 2 in PCL (polycaprolactone). These particles are incorporated in composites with GelMA 39 and release O 2 for up to 5 weeks. 40 Over 2 weeks, 2.5 μM of H 2 O 2 is released without the formation of MPs, whereas 1.0 μM of H 2 O 2 is released with the formation of MPs.…”
Section: Oxygen Released From Cpo Lignin Composites Was Maintained At...mentioning
confidence: 99%